Hepatocyte Nuclear Factor 4 alpha 2 Messenger RNA Reprograms Liver‐Enriched Transcription Factors and Functional Proteins in End‐Stage Cirrhotic Human Hepatocytes. Issue 11 (1st July 2021) - Tafaleng, Edgar N.; Mukherjee, Amitava; Bell, Aaron; Morita, Kazutoyo; Guzman‐Lepe, Jorge; Haep, Nils; Florentino, Rodrigo M.; Diaz‐Aragon, Ricardo; Frau, Carla; Ostrowska, Alina; Schultz, Joshua R.; Martini, Paolo G. V.; et al.
Abstract : The only definitive therapy for end‐stage liver disease is whole‐organ transplantation. The success of this intervention is severely limited by the complexity of the surgery, the cost of patient care, the need for long‐term immunosuppression, and the shortage of donor organs. In rodents and humans, end‐stage degeneration of hepatocyte function is associated with disruption of the liver‐specific transcriptional network and a nearly complete loss of promoter P1‐driven hepatocyte nuclear factor 4‐alpha (P1‐HNF4α) activity. Re‐expression of HNF4α2, the predominant P1‐HNF4α, reinstates the transcriptional network, normalizes the genes important for hepatocyte function, and reverses liver failure in rodents. In this study, we tested the effectiveness of supplementary expression of human HNF4α2 messenger RNA (mRNA) in primary human hepatocytes isolated from explanted livers of patients who underwent transplant for end‐stage irreversibly decompensated liver failure (Child‐Pugh B, C) resulting from alcohol‐mediated cirrhosis and nonalcoholic steatohepatitis. Re‐expression of HNF4α2 in decompensated cirrhotic human hepatocytes corrects the disrupted transcriptional network and normalizes the expression of genes important for hepatocyte function, improving liver‐specific protein expression. End‐stage liver disease in humans is associated with both loss of P1‐HNF4α expression and failure of its localization to the nucleus. We found that while HNF4α2 re‐expression increased the amount of P1‐HNF4α protein in hepatocytes, it did not alter the ability of hepatocytes to localize P1‐HNF4α to their nuclei. Conclusion: Re‐expression of HNF4α2 mRNA in livers of patients with end‐stage disease may be an effective therapy for terminal liver failure that would circumvent the need for organ transplantation. The efficacy of this strategy may be enhanced by discovering the cause for loss of nuclear P1‐HNF4α localization in end‐stage cirrhosis, a process not found in rodent studies. Abstract : Re‐expression of HNF4α2 in decompensated cirrhotic human hepatocytes corrects the disrupted transcriptional network and normalizes the expression of genes important for hepatocyte function, improving liver‐specific protein expression. mRNA‐mediated re‐expression of HNF4α2 in the livers of patients with the end‐stage disease may be an effective therapy for terminal liver failure that would circumvent the need for organ transplantation.